Relación entre el espacio escolar y el aprendizaje socioemocional en primera infancia : jardines infantiles en Colombia en un escenario no previsto (2020)
This research aims to explore the correlation between childhood's learning environments and socioemotional learning. This correlation was affected by the confinement, isolation and biosafety measures caused by Covid-19 pandemic. The following study analyzes that correlation in light of kindergartens comeback to face-to-face education. Inasmuch as learning environments offer conditions for socialization, interaction and emotional experiences, this research explores the possibility of rethinking kindergartens learning environments in a post pandemic scenario. Thus, this paper investigates the returning experience in an international and national context as well as focusing in Colombia where kindergartens have exceeded six months of enclosure. The research concludes with a diagnostic and possibilities to considerate in the kindergartens comeback in Colombia.